Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik SMP - Rahmadina Nasri; Elita Zusti Jamaan (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
The aim is to improve students' mathematical communication skills that are valid, practical and effective. Development research is carried out which produces student worksheets (LKPD) based on problem based learning (PBL). This development research using the Plomp model consists of three stages, namely, Preliminary research, Prototyping and Assessment. The research subjects were students of class VIII SMPN 17 Padang. The problem based learning model is a learning model that starts with problems that exist in the daily lives of students which has five stages, namely students are problem oriented, students are organized to learn, educators help independent and group investigations, students can develop and present the work and present it, and analyze and evaluate the problem solving process. LKPD validation is carried out by mathematics education experts, language experts and educational technology experts. The practicality of the LKPD is seen from the practicality questionnaire of students. The effectiveness of LKPD is seen from the competence of students which consists of aspects of attitudes, knowledge, and skills. Analysis of the validity data shows that the problem-based learning tool produced is valid. The results of practical data analysis show that the resulting learning tools are very practical. Learning tools have also been effective in student learning outcomes.